2013
DOI: 10.1007/s11255-013-0497-9
|View full text |Cite
|
Sign up to set email alerts
|

Ferroportin in monocytes of hemodialysis patients and its associations with hepcidin, inflammation, markers of iron status and resistance to erythropoietin

Abstract: Decreased ferroportin in monocytes of HD patients accompanies increased hepcidin, inflammation, decreased iron availability and is correlated with resistance to rHuEpo treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Its potential use in our patients needs to be explored. However, recent studies have shown that there was no correlation between hepcidin levels and other markers of iron stores and function, casting doubts on its potential usefulness in hemodialysis patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its potential use in our patients needs to be explored. However, recent studies have shown that there was no correlation between hepcidin levels and other markers of iron stores and function, casting doubts on its potential usefulness in hemodialysis patients …”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that there was no correlation between hepcidin levels and other markers of iron stores and function, casting doubts on its potential usefulness in hemodialysis patients. 31,[37][38][39] The safety of giving iron to patients with low TSAT and ferritin above 1200 µg/L in our or similar circumstances will need further evaluation. High ferritin has been linked to all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Eleftheriadis et al, 29 ESA resistance was found to be negatively correlated with ferritin, and transferrin saturation. However, in our study, ERI was not found to be associated with these iron parameters.…”
mentioning
confidence: 91%
“…On the other hand, Eleftheriadis et al , in a study performed in HD patients after a washout period from iron treatment indicated that serum hepcidin was related neither to serum iron, TSAT, EPO resistance index nor to IL‐6. In that study, serum hepcidin was not related even to the ferroportin expression in monocytes . Damien.…”
Section: Discussionmentioning
confidence: 73%